Introducing an index on prediction of post-revascularization cerebral infarction using preoperative CT perfusion parameters in moyamoya disease - Xiaojun Hao; Chao Zhang; Chen Yang; Xintong Zhao; Yunfeng Zhou; Juan Wang (Insights into Imaging)
Abstract Objective To determine the value of preoperative CT perfusion (CTP) parameters for prediction of post-revascularization cerebral infarction (post-CI) in adults with moyamoya disease (MMD). Methods This retrospective study included 92 adults with MMD who underwent surgical revascularization. Preoperative quantitative CTP parameters, including cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), time to drain (TTD), and transit time to maximum of the residue function (Tmax), along with clinical data, were compared between the groups with and without post-CI. Predictors of post-CI were identified and assessed using multivariable logistic regression and receiver-operating characteristic curve analyses. Results Post-CI occurred in 11 patients (12.0%). In univariate analysis, preoperative mean values for CBF, MTT, TTD, Tmax, initial presentation, infarction within the 2 months before surgery, surgical side, and modified Rankin Scale score on admission were associated with post-CI (all p < 0.05). Multivariable logistic regression revealed that the preoperative mean Tmax (OR 2.342, 95% CI: 1.267–4.330, p = 0.007) and infarction within the 2 months before surgery (OR 14.345, 95% CI: 2.108–97.638, p = 0.006) were independent predictors of post-CI. The preoperative mean Tmax produced the largest area under the curve (0.955, 95% CI: 0.914–0.997) with a cutoff of 3.590 s (sensitivity, 100%; specificity, 87.7%). Conclusions Adults with MMD are at risk of post-CI when the preoperative mean Tmax is > 3.590 s. Cerebral infarction during the 2 months before revascularization is also a risk factor for post-CI. Critical relevance statement Post-CI is a serious complication for adults with MMD following surgical revascularization. The risk of post-CI can be predicted using preoperative CTP parameters, which will assist neurosurgeons with surgical decisions and implementing individualized prophylactic strategies. Key Points Predicting the risk of post-CI in MMD patients is beneficial to their prognosis. The preoperative mean Tmax was an excellent perfusion parameter for predicting post-CI. Preoperative CTP evaluation can help clinicians make cautious surgical decisions. Graphical Abstract